Internal and external North Atlantic Sector variability in the Kiel Climate Model - Mojib Latif; Wonsun Park; Hui Ding; Noel S. Keenlyside (Meteorologische Zeitschrift, 2009)
The internal and external North Atlantic Sector variability is investigated by means of a multimillennial control run and forced experiments with the Kiel Climate Model (KCM). The internal variability is studied by analyzing the control run. The externally forced variability is investigated in a run with periodic millennial solar forcing and in greenhouse warming experiments with enhanced carbon dioxide concentrations. The surface air temperature (SAT) averaged over the Northern Hemisphere simulated in the control run displays enhanced variability relative to the red background at decadal, centennial, and millennial timescales. Special emphasis is given to the variability of the Meridional Overturning Circulation (MOC). The MOC plays an important role in the generation of internal climate modes. Furthermore, the MOC provides a strong negative feedback on the Northern Hemisphere SAT in both the solar and greenhouse warming experiments, thereby moderating the direct effects of the external forcing in the North Atlantic. The implications of the results for decadal predictability are discussed.